INTEGRATED MECHANISM FOR DEVELOPING THE MARKETING POTENTIAL OF HIGHER EDUCATION INSTITUTIONS BASED ON BENCHMARKING - BANZELIUK, I. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the essence of the concept of "mechanism" and its interpretation. The necessity of forming a comprehensive mechanism for developing the marketing potential of higher education institutions to improve the level of quality of education and competitiveness in the international market of educational services is substantiated.The purpose of the functioning of the integrated mechanism is defined as the harmonious development of marketing potential at all levels of its formation to ensure the evolution of all components of the marketing potential of higher education institutions through benchmarking to achieve the socio-economic development of the higher education system of Ukraine. The necessity of decomposing the proposed integrated mechanism for developing marketing potential into organizational, gender-behavioral, finance-economic mechanisms, due to the link to the functional diversity of tasks assigned to it, is substantiated. It is proposed to use benchmarking as a tool for developing the marketing potential of higher education institutions, which provides the implementation of successful practices of leaders of educational and other economic environments into the activities of higher education institutions. A separate and necessary element of the proposed integrated mechanism is information support for development, which allows creating reliable channels of communication between the internal environment and the external one, as well as influencing the economic decisions of consumers of educational services. As a result of the use of benchmarking, the effective functioning of an integrated mechanism for developing the marketing potential of higher education institutions is carried out based on benchmarking, which allows the higher education system to get an economic effect, which is manifested in an increase in revenues from the provision of paid services and the number of sources of financing, a rational distribution of funds between key resources of marketing potential, and increased labor productivity.
Keywords: development; marketing potential; institution of higher education; mechanism of development of marketing potential; benchmarking